2016
DOI: 10.1515/anre-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin E in Northeast India: A review on its origin, distribution, migration and health implication

Abstract: A systematic review of the studies on hemoglobin E in Northeast India has been carried out to understand the magnitude of research undertaken on this aspect during the last seven decades. Owing to the high prevalence of hemoglobin E in this part of India different authors have studied this hemoglobin from different perspectives and found conflicting results. However a systematic review of such studies is lacking from a holistic point of view. Most of the epidemiological, in vitro as well as in vivo studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
1
Order By: Relevance
“…Assam has a mixed population with an ethnic link of Southeast Asia, Aryans, immigrant Oryahs comprising the tea garden laborers, migrating population from other states, Bengalis. [3] In our study, the prevalence of hemoglobinopathies was almost 35.0% while the study by Warghade et al for abnormal Hb had shown a rate of 18.44% and Sanghavi et al as 27%. [4,5] In the study by Warghade et al, a large population (n = 65779) from all over India of all age groups was screened to identify Hb fractions prevalent in India whereas our study incorporated a small number (n = 206) of sick children, specifically suffering from chronic anemia and resident of a state which is a known reservoir for hemoglobinopathies.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Assam has a mixed population with an ethnic link of Southeast Asia, Aryans, immigrant Oryahs comprising the tea garden laborers, migrating population from other states, Bengalis. [3] In our study, the prevalence of hemoglobinopathies was almost 35.0% while the study by Warghade et al for abnormal Hb had shown a rate of 18.44% and Sanghavi et al as 27%. [4,5] In the study by Warghade et al, a large population (n = 65779) from all over India of all age groups was screened to identify Hb fractions prevalent in India whereas our study incorporated a small number (n = 206) of sick children, specifically suffering from chronic anemia and resident of a state which is a known reservoir for hemoglobinopathies.…”
Section: Discussioncontrasting
confidence: 43%
“…Tea garden community consists of tribal population, originally from Orissa, Chotanagpur, Andhra Pradesh, and Jharkhand where HbS gene is more common than others. [3,15] In the hematological parameters, we found that mean Hb for BTM and SCD was 5.3 ± 0.7 g/dl and 6.0 ± 0.0 g/dl, respectively. Sanghavi et al reported quite similar values for mean Hb of 6.28 ± 1.75 g/dl and 6.5 ± 1.7 g/dl, respectively, for BTM and SCD.…”
Section: Discussionmentioning
confidence: 96%
“…Hemoglobin E (HbE) is a hemoglobin variant caused by a point mutation in codon 26 of the b-globin gene which substitutes lysine for glutamic acid. HbAE is most common in Southeast Asia, especially northeast and eastern India and eastern Thailand [3] where more than 50% of some populations have HbAE [4]. In addition, HbAE is also prevalent in Myanmar, Indonesia, and Malaysia [3].…”
mentioning
confidence: 99%